ANALISIS TINGKAT KEPUASAN PENGUNJUNG PASAR INDUK DAN PASAR DADAKAN (PASAR TUMPAH) DI SANGATTA UTARA - Simunawir Sitoro (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2022)
The purpose of this study is to find out and analyze whwther there are differences in visitor satisfaction in shopping at the impromptu market (spill market) and the main market in North sangatta. The type of research used is comparative. The sample in this study was 100 respondents divided into two, 50 respondents for buyers who werw shopping at the North sangatta main market and 50 respondents for buyers who were at the impromptu market (spilled market) in North sangatta. The instrument testing tecgnique in this research is validity test and reliability test, while the data analysis technique uses descriptive statistical analysis test and umpaired average t-test. The results showed that there were differences in the satisfaction of visitors who shopped between the main market or at the impromptu market (spilled market) in North Sangatta, East Kutai Regency